Income inequality and willingness to pay for public environmental goods - Stefan Baumgärtner; Moritz A. Drupp; Jasper N. Meya; Jan M. Munz; Martin F. Quaas (Kiel University, Department of Economics, 2016)
We study how the distribution of income among members of society, and income inequality in particular, affects social willingness to pay (WTP) for environmental public goods. We find that social WTP for environmental goods increases with mean income, and decreases (increases) with income inequality if and only if environmental goods and manufactured goods are substitutes (complements). Furthermore, social WTP for environmental normally changes more elastically with mean income than with income inequality. We derive adjustment factors for benefit transfer to control for differences in income distributions between a study site and a policy site. For illustration, we quantify how social WTP for environmental public goods depends on the respective income distribution for empirical case studies in Sweden, China and the World. We find that the effects of adjusting for income inequality can be substantial.
Keywords: Q51; D63; H23; H43; 330; environmental goods; public goods; income distribution; inequality; willingness to pay; benefit transfer; sustainability policy